Global CO2 emissions from cement production, 1928–2017 - Andrew, Robbie M (Earth system science data, 2018)
Global production of cement has grown very rapidly in recent years, and after fossil fuels and land-use change, it is the third-largest source of anthropogenic emissions of carbon dioxide. The availability of the required data for estimating emissions from global cement production is poor, and it has been recognised that some global estimates are significantly inflated. Here we assemble a large variety of available datasets, prioritising official data and emission factors, including estimates submitted to the UNFCCC plus new estimates for China and India, to present a new analysis of global process emissions from cement production. We show that global process emissions in 2017 were 1.48±0.20 Gt CO2, equivalent to about 4 % of emissions from fossil fuels. Cumulative emissions from 1928 to 2017 were 36.9±2.3 Gt CO2, 70 % of which have occurred since 1990. Emissions in 2016 were 28 % lower than those recently reported by the Global Carbon Project. The data associated with this article can be found at https://doi.org/10.5281/zenodo.831454.